The granulocyte colony-stimulating factor produced during Streptococcus suis infection controls neutrophil recruitment in the blood without affecting bacterial clearance - Bleuzé, Marêva; Lehoux, Mélanie; Auger, Jean-Philippe; Gottschalk, Marcelo; Segura, Mariela (Frontiers in Immunology, 2024)
Streptococcus suis causes diseases in pigs and has emerged as a zoonotic agent. When infected, the host develops an exacerbated inflammation that can lead to septic shock and meningitis. Although neutrophils greatly infiltrate the lesions, their dynamics during S. suis infection remain poorly described. Moreover, very few studies reported on the production and role of a key factor in the regulation of neutrophils: the colony-stimulating granulocyte factor (G-CSF). In this study, we characterized the G-CSF ̶ neutrophil axis in the pathogenesis of S. suis induced disease. Using a mouse model of S. suis infection, we first evaluated the recruitment of neutrophils and their activation profile by flow cytometry. We found that infection provokes a massive neutrophil recruitment from the bone marrow to the blood and spleen. In both compartments, neutrophils displayed multiple activation markers. In parallel, we observed high systemic levels of G-CSF, with a peak of production coinciding with that of neutrophil recruitment. We then neutralized the effects of G-CSF and highlighted its role in the release of neutrophils from the bone marrow to the blood. However, it did not affect bacteremia nor the cytokine storm induced by S. suis. In conclusion, systemic G-CSF induces the release of neutrophils from the bone marrow to the blood, but its role in inflammation or bacterial clearance seems to be compensated by unknown factors. A better understanding of the role of neutrophils and inflammatory mediators could lead to better strategies for controlling the infection caused by S. suis.